Law Enforcement On Deforestation Forests Conservation In Indonesia - Panggung Handoko (International Journal Of Community Service, 2023)
This research aims to analyze the application of multi-layered crimes in cases of environmental damage as in the case in the Malang District Court decision Number: 76/Pid.B/LH/2022/PN Mlg. with the occurrence of two criminal acts, namely not having a mining permit in a forest area and an act that intentionally caused forest damage. The formulation of the problem in this research is the qualifications of criminal acts of environmental damage and what the judge considers in imposing multiple criminal sanctions in case number: 76/Pid.B/LH/2022/PN Mlg. This research uses normative juridical research methods, as well as using a statutory approach and a case approach.Based on the results of the research and discussion, to determine whether damage to protected forests has occurred is to qualify the criminal act of environmental damage that has been carried out, that the elements of the criminal act related to the subject are defined as the party responsible, there is an element of error by knowing that the criminal act has been committed, the act that is unlawful, namely as violating the provisions in Article 89 paragraph (1) letter a jo. Article 17 paragraph (1) letter b of Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction related to carrying out mining in forest areas without the Minister's permission and Article 98 paragraph (1) of Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management by exceeding ambient air quality standards, water quality standards, sea water quality standards, or standard criteria for environmental damage and the implementation of concurrent actions (a real collision) is closely related to this research.